Cardiac manifestations of inherited metabolic disease in children. Issue 5 (May 2017) - Lloyd, David FA; Vara, Roshni; Mathur, Sujeev
Abstract: Inborn errors of metabolism (IEM) are responsible for around 5% of all cases of cardiomyopathy (CM) and for 15% of non‐idiopathic cases. Storage disorders such as Pompe disease (glycogen storage disease type II) typically cause hypertrophic CM, whereas the accumulation of toxic metabolites, as seen in the organic acidurias, is associated with dilated cardiomyopathy (DCM). Mixed pathology is also possible, particularly in late presentations. IEM such as Barth syndrome, a disorder of cardiolipin stability usually associated with DCM, have been associated with rarer types of CM such as endocardial fibroelastosis and left ventricular non‐compaction. Conduction disturbances can also occur, particularly in disorders of glycogen metabolism associated with PRKAG2 mutations. Cardiac screening of patients with metabolic diseases is important to guide treatment and stratify risk. Supportive cardiac treatment may be required, and although associated myocardial disease may improve or even resolve with correction of the underlying metabolic disturbance, progression to cardiac transplantation has been described. In this article we document all IEM known to be associated with cardiac disease in children, focusing on common and clinically important diagnoses. We also discuss the pathophysiology of the various types of CM, and present a recommended approach to screening in the pediatric population.